ANALISIS RUGI DAYA DAN REKONSILIASI ENERGI JARINGAN DISTRIBUSI TEGANGAN MENENGAH 20 KV PADA PENYULANG NIJANG - Jaya, Ahmad; Wirentake (Jurnal TAMBORA, 2020)
This study aims to determine the loss / power loss in the nijang feeder through the energy reconciliation process, simulation of the ETAP 12.6 program, and manual calculations. The benefits of this research can be used as a basis for consideration of the improvement efforts that should be carried out to minimize power losses in the medium voltage distribution network of Nijang feeders. The method used is quantitative research method because it takes data from the measurement of the transaction point which is then compared with the results in the simulation program ETAP 12.6 and manual calculations. The results showed that the power loss (kWh) resulted from 3 processes showed that the energy reconciliation process resulted in a greater power loss, namely 10,657 kWh, the ETAP 12.6 simulation resulted in a power loss of 3049 kWh and in manual calculations it resulted in losses. power of 4199 kWh, from the results of the research it can be seen that in the simulation process ETAP 12.6 and manual calculations only calculate power losses due to technical causes, while the energy reconciliation process includes technical and non-technical causes. It is hoped that this research can support efforts to improve power losses / losses in the PT PLN (Persero) UP3 Sumbawa environment.